On African Theology - Hastings, Adrian (Scottish journal of theology, 1984)
Edward Schillebeeckx in The Understanding of Faith (1974, 154) defined or described theology as ‘the critical self-consciousness of Christian praxis in the world and the church’. Others may prefer another definition, but it can be agreed that Christian theology is not revelation and it is not church doctrine; both of these while inevitably formulated within time yet lay claim to, and acquire, a certain degree of timelessness which is neither possible nor desirable for ‘theology’. Theology rather requires a continuous contemporaneity. It is a ‘critical self consciousness’ — an extended intelligent response of men of faith both to the word of God and to their own world. At times it may appear to concentrate more upon that word, as found in the Scriptures, while interpreting and applying it aptly and acutely in the light of contemporary culture; at other times theology will appear to concentrate more upon the contemporary world, or upon some part of it decisively significant for this theologian or the group of christians of which he or she forms part, interpreting it and judging it in the light of scripture. Behind appearances theology, to be true to itself, has always to do both.